On vibration mitigation and energy harvesting of a non-ideal system with autoparametric vibration absorber system - Felix, Jorge Luis Palacios; Balthazar, Jose Manoel [UNESP]; Rocha, Rodrigo Tumolin; Tusset, Angelo Marcelo; Janzen, Frederic Conrad (Springer Nature, 2018)
This paper demonstrates that vibration mitigation and energy harvesting can be achieved simultaneously by using of an electricity-generating from autoparametric vibration absorber system (AVAS) and non-ideal system (NIS). The NIS consists of a simple portal frame excited by a small dc motor with eccentric mass, with limited power supply and located on the top. The AVAS consists of a cantilever beam with tip mass parallel coupled to NIS. A piezoelectric material is considered for energy harvesting installed in the base of the AVAS and an electric circuit is connected to the piezoelectric material in order to produce voltage output. Several numerical simulations were carried out focusing on the passage through the resonance of NIS, when the motor rotational frequency is near the portal frame natural frequency and when the non-ideal subsystem frequency is approximately twice the absorber beam frequency (two-to-one internal resonance). The results showed the existence of Sommerfeld effect in NIS and saturation phenomenon in the NIS–AVAS.
Keywords: Autoparametric absorber; Energy harvesting; Non-ideal vibration; Saturation phenomenon